On the Acoustics of Emotion in Audio: What Speech, Music, and Sound have in Common - Weninger, Felix; Eyben, Florian; Schuller, Björn W.; Mortillaro, Marcello; Scherer, Klaus R. (Frontiers in Psychology, 2013)
Without doubt, there is emotional information in almost any kind of sound received by humans every day: be it the affective state of a person transmitted by means of speech; the emotion intended by a composer while writing a musical piece, or conveyed by a musician while performing it; or the affective state connected to an acoustic event occurring in the environment, in the soundtrack of a movie or in a radio play. In the field of affective computing, there is currently some loosely connected research concerning either of these phenomena, but a holistic computational model of affect in sound is still lacking. In turn, for tomorrow’s pervasive technical systems, including affective companions and robots, it is expected to be highly beneficial to understand the affective dimensions of ’the sound that something makes’, in order to evaluate the systems auditory environment and its own audio output. This article aims at a first step towards a holistic computational model: Starting from standard acoustic feature extraction schemes in the domains of speech, music, and sound analysis, we interpret the worth of individual features across these three domains, considering four audio databases with observer annotations in the arousal and valence dimensions. In the results, we find that by selection of appropriate descriptors, cross-domain arousal and valence regression is feasible achieving significant correlations with the observer annotations of up to .78 for arousal (training on sound and testing on enacted speech) and .60 for valence (training on enacted speech and testing on music). The high degree of cross-domain consistency in encoding the two main dimensions of affect may be attributable to the co-evolution of speech and music from multimodal affect bursts, including the integration of nature sounds for expressive effects.